Traps efficiency in the capture of Xylosandrus compactus (Eichhoff, 1875) (Coleoptera: Curculionidae: Scolytinae) during the early development of Aniba rosaeodora Ducke (Research, Society and Development, 2022)
Xylosandrus compactus (Coleoptera: Curculionidade: Scolytinae) is a pest insect with widespread occurrence in 114 countries, causing damage to both seedlings and trees production of approximately 220 species, including Aniba rosaeodora Ducke (Rosewood). In Brazil, X. compactus already occurs in the states of Amazonas, Bahia, Espírito Santo, Minas Gerais, Pará, Rondônia and Tocantins. Due to the difficulty of handling this pest, this study aimed to evaluate the efficiency of the Carvalho-47, IAPAR, and PET-SM traps, using 30 ml of bait, with it being 70° alcohol or a mixture of methanol and 70° alcohol (3:1). The collections were carried out weekly over for 12 months. The experiment was conducted in a Completely Randomized Design (CRD) in a 3 x 2 factorial scheme (3 types of traps x 2 types of bait) with 4 repetitions each. After one year of monitoring, 2.463 individuals were captured, recording reduced losses of 21.42% in the seedling production of A. rosaeodora. There was no statistically significant interaction between traps and baits. The bait composed by methanol plus 70° alcohol was more efficient than the use of 70° alcohol alone. IAPAR and PET-SM trap models were more efficient in capturing X. compactus. Therefore, we recommend these two models, using methanol plus 70° alcohol as bait, to reduce investment costs in ineffective insecticides and avoid losses in seedling production.